2019
DOI: 10.1002/cnm.3205
|View full text |Cite
|
Sign up to set email alerts
|

Does the transversal screw design increase the risk of mechanical complications in dental implants? A finite elements analysis

Abstract: The transversal screw was introduced in order to overcome some disadvantages of the transocclusal screw. However, its mechanical risk has not been studied sufficiently. The main purpose of this research was to assess and compare stress distribution in the screws and abutment of a single-crown implant with transversal and transocclusal screw models. Two 3D models were assembled to analyse a single-implant-supported prosthesis with transversal and transocclusal screws embedded in the jawbone. The crown was subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Considering that each tooth has the same characteristic shape as its standard tooth of the same name, bionic geometry morphology design-based methods tend to adopt the standard dental to design crown [ 12 , 42 ]. In the process of crown design, occlusal fingerprint is necessary to fully reflect the functional characteristics of the occlusal surface since it provides reference for the position and direction of the correct occlusal contacts [ 43 ]. If the occlusal fingerprint distribution is not considered during the design process, there will be a large amount of unreasonable interference areas on the designed crown.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that each tooth has the same characteristic shape as its standard tooth of the same name, bionic geometry morphology design-based methods tend to adopt the standard dental to design crown [ 12 , 42 ]. In the process of crown design, occlusal fingerprint is necessary to fully reflect the functional characteristics of the occlusal surface since it provides reference for the position and direction of the correct occlusal contacts [ 43 ]. If the occlusal fingerprint distribution is not considered during the design process, there will be a large amount of unreasonable interference areas on the designed crown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, experimental and clinical studies with Lateral-screw-retained implant design showed insufficient proof of the treatment reliability. In addition, to allow the screw to tighten with adequate torque, it was recommended that the crown should present at least the lingual face in metal, without esthetic veneering, since the lateral screw required fixation in both crown and abutment [ [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical benefits of using an extra component (lateral screw) in the prosthesis setup should be better addressed, demonstrating the reduction of stress magnitude and increasing the safety factor for fracture incidence. A previous finite element analysis reported that the conventional prosthetic transversal screw is an option to reduce the risk of mechanical complications, both in the prosthetic screw and in the abutment screw [ 15 ]. However, both models considered in the reported investigation presented a lateral screw, and the comparison with the conventional cement-retained and screw-retained designs was not performed [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detecting stress on implant-supported prostheses and analyzing its distribution to the implants have a fundamental importance for the evaluation of both the stresses applied on the implants and the design of the structure. It is important to evaluate different stresses generated on the implants by different loads [6,7].…”
Section: Introductionmentioning
confidence: 99%